Synergizing Solar Cell Technology, Radio Wave Communication, AI Integration, and Business Opportunities: A Comprehensive Review - Chen jin Kim (International Journal of Multidisciplinary Sciences and Arts, 2024)
We are at a turning point in our quest for more sustainable energy options, improved connection, and technical innovation as solar cell technology, radio wave communication, artificial intelligence (AI), and economic potential come together. This study explores the complex interactions between these integrated technologies, examining all of their facets, from practical difficulties to ethical issues to future opportunities. The impact of artificial intelligence (AI) on solar energy management is first discussed in the study, with a focus on how AI-driven systems improve energy storage, maximize energy capture, and adjust to changing weather. Simultaneously, the function of AI in radio wave communication networks is elucidated, encompassing spectrum management, cyber security, and quality of service. The foundation of the burgeoning smart grid and Internet of Things (IoT) age is the integration of AI with radio waves and solar cells, which promotes energy efficiency and system resilience while permitting fine-grained control over energy use. As these technologies merge, the conversation moves to the business sector, where it examines market trends and investment prospects. These integrated systems are becoming more and more necessary as sustainability, connectedness, and energy efficiency open up new opportunities for businesses, investments, and environmentally friendly real estate development. Green financing and solar-as-a-service (SaaS) are two examples of sustainable business concepts that are becoming increasingly important in the changing business environment. These encouraging advancements are not without difficulties, though. Significant obstacles include those related to technical integration, data protection, regulatory compliance, environmental effect, and the digital divide. As technology develops, moral issues become increasingly important.